Modulating Electromagnetic Genes Through Bi-Phase High-Entropy Engineering Toward Temperature-Stable Ultra-Broadband Megahertz Electromagnetic Wave Absorption - Xiaoji Liu; Yuping Duan; Nan Wu; Guangming Li; Yuan Guo; Jiangyong Liu; Ning Zhu; Qiang Wang; Lin Wang; Zichen Xu; Hao Wei; Guojun Wang; et al. (Nano-Micro Letters)
Highlights The bi-phase FeCoNiCr0.4Cu0.2/(FeCoNiCrCu)3O4 high-entropy composites are innovatively constructed for the first time by low-temperature oxygen bath strategy. The bi-phase high-entropy composites (BPHEC) can precisely regulate the electromagnetic genes, realizing the ideal ultra-broadband and temperature-stable electromagnetic wave absorption. Simultaneously, the formation mechanism of BPHEC during low-temperature oxygen bath and the regulation mechanism of electromagnetic genes are elucidated.